Experiential Learning Practices and Performance in BSBA Marketing Management Program: Its Preparedness for Student Internship - Calumpiano, Mearelle; Carlon, Joshua; Garcia, Joy Evelyn; Gozom, Clarisa; Lorenzo, John Anthony; Silva, Jhena Eunice (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined experiential learning practices, academic performance, and preparedness for student internship among Bachelor of Science in Business Administration major in Marketing Management students at Eulogio “Amang” Rodriguez Institute of Science and Technology. Anchored in experiential learning principles, it determined the extent of practical learning activities, assessed students’ academic performance and internship preparedness, and tested the relationships among these variables. A descriptive-correlational research design was used. The respondents included 124 BSBA Marketing Management students and 20 faculty members handling marketing courses, selected through purposive sampling. Data were gathered using a structured researcher-made questionnaire and analyzed through percentage, weighted mean, overall weighted mean, and Pearson Product-Moment Correlation Coefficient at the 0.05 level of significance. Experiential learning practices obtained an overall weighted mean of 4.17 and were interpreted as practiced, with participation in marketing competitions and seminars receiving the highest rating and on-the-job training simulations receiving the lowest. Academic performance obtained an overall weighted mean of 4.14 and was rated very good, while internship preparedness obtained an overall weighted mean of 4.29 and was interpreted as highly prepared. Experiential learning practices showed a weak and nonsignificant relationship with academic performance and a negligible and nonsignificant relationship with internship preparedness. Academic performance also showed a moderate but nonsignificant relationship with internship preparedness. The findings indicate that students’ academic achievement and internship readiness may also be influenced by personal, educational, and environmental factors beyond experiential learning practices. The study recommends strengthening simulations, industry immersion, academic interventions, technical training, mentoring, and professional development activities. It supports SDG 4 on Quality Education and SDG 8 on Decent Work and Economic Growth by promoting competency-based education and workforce readiness. Its sustainability contribution lies in improving curriculum delivery, institutional support, and alignment between academic preparation and professional demands.